Suprasellar Ganglioglioma: Expanding the Differential Diagnosis - Isabella Tondi Resta; Arminder Singh; Bruce C. Gilbert; Mumtaz V. Rojiani; Cargill Alleyne; Amyn M. Rojiani (Case Reports in Pathology)
This case study describes a young man with symptoms suggestive of the presence of a space-occupying lesion within the cranial cavity. Imaging studies confirmed a lesion in the suprasellar region and surgical intervention to remove the tumor yielded an unexpected diagnosis. Neuroimaging characteristics and histopathology including immunohistochemistry are described. Gangliogliomas are uncommon CNS neoplasms and are most commonly found in the temporal and frontal lobes of young, male adults. They are rarely seen in the suprasellar region and only a handful of cases have been reported to date. The differential diagnoses associated with these suprasellar region lesions can be dependent on the age of the patient and neuroimaging characteristics. The present report highlights the importance of histopathological examination and the need to consider a wide range of diagnostic entities in the differential diagnosis of lesions in this topographic distribution, including rarely encountered tumors such as gangliogliomas.